2010
DOI: 10.3346/jkms.2010.25.9.1291
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Specific Membrane Antigen mRNA in Blood as a Potential Predictor of Biochemical Recurrence after Radical Prostatectomy

Abstract: We investigated whether the detection of prostate specific membrane antigen (PSMA) in blood preoperatively has predictive value for biochemical recurrence (BCR) after radical prostatectomy in patients with prostate cancer. All 134 patients scheduled to receive radical prostatectomy for prostate cancer were prospectively enrolled. The authors used nested reverse transcriptase-polymerase chain reaction (RT-PCR) assay to detect PSMA mRNA-bearing cells in peripheral blood, and analyzed the ability of PSMA mRNA pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…PSMA is known to be over-expressed in advanced PC or mCRPC [33]. While strong PSMA expression in the tumor has been associated with higher tumor stages, Gleason Scores, preoperative PSA levels, HER2 expression, and a higher risk of biochemical recurrence [34], there is no correlation between blood PSMA mRNA and tumor stage, Gleason score, or serum PSA [35]. However, it has been shown that the detection of the PSMA mRNA in blood can predict biochemical recurrence after radical prostatectomy [35].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PSMA is known to be over-expressed in advanced PC or mCRPC [33]. While strong PSMA expression in the tumor has been associated with higher tumor stages, Gleason Scores, preoperative PSA levels, HER2 expression, and a higher risk of biochemical recurrence [34], there is no correlation between blood PSMA mRNA and tumor stage, Gleason score, or serum PSA [35]. However, it has been shown that the detection of the PSMA mRNA in blood can predict biochemical recurrence after radical prostatectomy [35].…”
Section: Discussionmentioning
confidence: 99%
“…While strong PSMA expression in the tumor has been associated with higher tumor stages, Gleason Scores, preoperative PSA levels, HER2 expression, and a higher risk of biochemical recurrence [34], there is no correlation between blood PSMA mRNA and tumor stage, Gleason score, or serum PSA [35]. However, it has been shown that the detection of the PSMA mRNA in blood can predict biochemical recurrence after radical prostatectomy [35]. Furthermore, PSMA expression in CTCs is characterized by a high intra-patient heterogeneity and is found in a large portion (67%) of metastatic PC patients by the CellSearch ® assay [36].…”
Section: Discussionmentioning
confidence: 99%
“…7). 86,87 Only recently, PSMA-targeted therapies labelled with beta emitters like Lutetium-177 ( 177 Lu) for radioligand therapy have emerged as a promising therapeutic option for patients with mCRPC. 88,89 Patients are screened for eligibility according to high PSMA uptake in the metastases as detected by 68 Ga-labelled PSMA-positron emission tomography ( 68 Ga-PSMA-PET).…”
Section: Prostate-specific Membrane Antigenmentioning
confidence: 99%
“…In the study with 250 high-risk patients with PC, presence of prostate stem cell antigen (PSCA) mRNA in the peripheral blood was reported to be a significant predictor of biochemical recurrence after radical prostatectomy (HR, 4.549; 95% CI, 1.685–12.279) [ 93 ]. Joung et al reported that prostate specific membrane antigen (PSMA) mRNA in the peripheral blood was a predictor of biochemical recurrence after radical prostatectomy [ 95 ]. Nested RT-PCR assay detecting PSMA mRNA-bearing cells in the peripheral blood was employed to detect CTCs.…”
Section: Application Of Ctcs In Pcmentioning
confidence: 99%